Paraneoplastic Syndrome: A Missed Diagnosis - Archana Kalaichelvam; Karunya Narayanasamy; Thinakarmani B. (Indian Journal of Medical and Paediatric Oncology)
Paraneoplastic syndrome can involve a single organ or diverse organ systems. It is one of the rare manifestations of occult malignancy. A 47-year-old female patient with history of recent suspected herpes infection presented with features of extensive skin darkening and thickening, associated with poor swallowing and cough reflex. Patient was not able to lift both arms nor able to sit or stand which was suggestive of proximal muscle weakness involving the shoulders and hip. Patient's initial workup for autoimmune disorders including dermatomyositis was negative. With paraneoplastic syndrome as differential diagnosis contrast-enhanced computed tomography chest and abdomen and tumor markers CA125 and CA19.9 done showed no evidence of occult malignancy. Patient was started on empirical steroids for polyradiculoneuropathy. After starting steroids patients was able to sit and walk with support. Patient was able to swallow liquids without aspiration. On regular follow-up over a period of 3 months, patient developed abdomen pain and abdominal distention which on evaluation showed ascites and multiple new cystic ovarian lesions suggestive of ovarian malignancy. Patient's CA125 was repeated and was markedly elevated. Patient was referred to an oncologist and was started on chemotherapy along with immunosuppressants. This case report emphasizes the need for regular follow-up of patients suspected of paraneoplastic syndrome. Although the initial workup for malignancy did not give a clue, on periodic review we were able to make the primary diagnosis and start appropriate treatment and achieve a better patient survival.